Scanning acoustic microscopy of polymeric materials and biological substances - MAYEV, Roman Gr. (Archives of Acoustics, 1988)
For the last few years a new method of visualization and quantitative analysis of physico-mechanical properties and microstructure of heterogenetic media — the acoustic microscopy — has been intensively elaborated in the world. In this method waves of ultrasound and hypersound range are used as an analysis factor. It allows to use this method for investigating a wide variety of opaque materials and goods and obtaining information about their inner structures as well as for optically transparent materials in which the contrast between different structures is practically absent. In both cases an investigator receives information that is quite different from that obtained with the help of other methods, namely, the distribution of local physico-mechanical properties for example, bulk compression, shift, etc. in the material of the sample. We give a review of the results of the work on methods and means of acoustic microscopy, worked out in the Centre for Acoustic Microscopy of the USSR Academy of Sciences for investigation of polymeric composites and biological objects as well as the results of analogical investigations of the loading scientific centres in the world. We set forth common physical basis and principles of getting acoustic images as well as the methods of studying microstructures and mechanical properties of heterogenetic objects with the help of acoustic microscope.